A broad range: From simple and brief to intensive single‐session interventions: Commentary on Schleider et al. (2023). Issue 5 (6th April 2023) - Ghaderi, Ata; Welch, Elisabeth
Abstract: To push research and treatment in the field of eating disorders (EDs) forward, we need to not only systematically develop our current knowledge and skills through established procedures for research and clinical practice, but also make room for disruptive innovations and thinking out of the box. The paper by Schleider et al. (2023, International Journal of Eating Disorders ) provides a thoughtful invitation to think differently by considering single‐session interventions (SSI) for prevention and treatment of EDs. Beyond expanding our intervention tools, SSI may force us to think more mechanistically about the processes of change, and about the format and delivery of our interventions, both for EDs and from a transdiagnostic perspective. In this commentary, we reflect on the possible benefits and implications of SSI, and the necessity of mechanistically driven and rigorous empirical research for developing efficacious SSI.